Creating an Adaptive Technology Using a Cheminformatics System To Read Aloud Chemical Compound Names for People with Visual Disabilities - Kamijo, Haruo; Morii, Shingo; Yamaguchi, Wataru; Toyooka, Naoki; Tada-Umezaki, Masahito; Hirobayashi, Shigeki (Journal of chemical education, 2016)
Various tactile methods, such as Braille, have been employed to enhance the recognition ability of chemical structures by individuals with visual disabilities. However, it is unknown whether reading aloud the names of chemical compounds would be effective in this regard. There are no systems currently available using an audio component to assist in the recognition of chemical structures. This study aims to establish the essential requirements for the prototype Chemical Literature Extraction and Aloud-reading System (CLeArS) that enables visually impaired people to recognize a depicted chemical structure after hearing its name, which complies with the nomenclature adopted by the International Union of Pure and Applied Chemistry. Details of the methods employed in CLeArS and its execution are presented, in addition to the fundamental requirements for recognizing chemical structures using CLeArS. Experimental results on 450 images comprising both simple and complex chemical structures show a high recognition rate of 90% among subjects with visual disabilities. Thus, we conclude that reading aloud the names of chemical compounds is an effective method enabling students with impaired vision to recognize chemical structures.